The psychological typology of juvenile offenders in bourgeois Lithuania - Endzinas , A. (Psichologija, 2016)
1. The so called progressive method of student division was used in juvenile education institutions in bourgeois Lithuania. Juvenile offenders in these institutions were divided into “free”, “supervized”, and “correctional” groups according to behavior. The new juvenile offenders were first assigned to "supervized" group and later to the “free” group, in which they had almost full freedom. They got later out to freedom from the “free” group. The head of Pedagogics Department in Kaunas University J. Vabalas-Gudaitis questioned the relevance of such system, and proposed to replace it with type classification based on psychological features. He called his new typology the “synergotypical classification of offenders” and published it in the journal “Forensic manual”. 2. J. Vabalas-Gudaitis typology consisted of three types of offenders: I. Mental – associative type II. Emotional – associative type III. Peripheral – associative type 3. The proposed classification of Professor J. Vabalas-Gudaitis was introduced into one of juvenile education institutions in Kalnaberze. Since every type needed different kind of work, the offenders were divided into three groups. Educations assigned to different groups had to behave themselves in accordance to group psychological features. In order to carry out psychological research and collect corresponding data, a separate group with an assigned educator was formed. Juvenile offenders were initially assigned into this group; dominating character features were determined, personal file was started, medical investigation was carried out by a doctor and the offender was assigned to a corresponding group. The initial assigning was not accurate at all times and sometimes the juvenile offenders must have been transferred into the other group. 4. The treatment methods were used according to the psychological types: in mental – associative group the attention was focused on the development of feelings of honor and worth; in emotional – associative group – to the ability of self-control, temper, and self-restraint. The program efficacy was reduced by the wide spectrum of the age of offenders: juvenile offenders in Kalnaberze educational institution was from 10 to 14 years of age.
Keywords: juvenile offenders; education